Not How the World Is, but That It Exists: Wittgenstein on the Mystical and the Meaningful - Rump, Jacob (Mysticism and meaning, 2019)
Wittgenstein's conception of the mystical should not be understood as referring to a realm of fundamental but ineffable facts or truths. Rather, it is a marker of that which makes facticity and truth possible. Questions of fundamental value ascription are beyond the teach of scientific or logical analysis